Changes in Magnetic Properties of Magnetite Nanoparticles Upon Microbial Iron Reduction. (7th March 2022) - Wang, Pengcong; Shi, Taiheng; Mehta, Neha; Yang, Shanshan; Wang, Hongmei; Liu, Deng; Zhu, Zongmin
Abstract: The magnetic signals of magnetite nanoparticles (NPs) preserved in rocks, soils, and sediments are effective index for paleoenvironmental reconstruction. It has been demonstrated that magnetite NPs can serve as a terminal electron sink for the microbial respiration (i.e., microbial iron reduction). The magnetic properties of magnetite NPs may be altered by microbial iron reduction, which is a critical but often overlooked process in paleomagnetism. In this study, three magnetite NPs with different particle sizes were reduced by a dissimilatory iron‐reducing bacterium ( Shewanella oneidensis MR‐1) under a non‐growth condition mimicking that of the early Earth and modern oligotrophic environment. The changes in magnetic, chemical as well as crystallographic properties of the magnetite NPs during the microbial reduction process were examined. Our results showed that the bioreduction rate of magnetite NPs was mainly controlled by their particle size and redox state. In addition, the microbial iron reduction could affect both the crystallographic and magnetic properties of three types of magnetite NPs used herein. After bioreduction, the crystal lattice parameters and magnetic susceptibility of the magnetite NPs increased, while their remanence recording capability and coercivity decreased (i.e., "softer" magnetism). Furthermore, bioreduced magnetite NPs had a larger remanence loss near the Verwey transition region with low‐temperature magnetic analysis. These results indicate that the microbial reduction of magnetite NPs deserves attention when sedimentary magnetites are used in paleoenvironment reconstruction. Plain Language Summary: Natural magnetite nanoparticles (NPs) in rocks, soils, and sediments can record the paleoenvironment information when they were formed. Of note, in anaerobic post depositional environments, magnetite‐bound Fe (III) can act as an electron sink for iron‐reducing microorganisms. This microbe‐magnetite interaction has the potential to affect magnetic properties of magnetite NPs. In doing so, the original paleoenvironment information carried by magnetite NPs might also be rewritten. Therefore, to extract the paleoenvironment information from sedimentary magnetite NPs, we should understand the impact of bioreduction on natural magnetite NPs before burial diagenesis. Three magnetite NPs with different particle sizes were exposed to a typical dissimilatory iron‐reducing bacterium ( Shewanella oneidensis MR‐1) under a non‐growth condition mimicking that of the early Earth and modern oligotrophic environments. We examined the changes in magnetic, chemical as well as crystallographic properties of the magnetite NPs during the bioreduction process. Our study found that the bioreduction rate of magnetite NPs was mainly controlled by their particle size and redox state. After bioreduction, the magnetism of magnetite NPs became "softer." These results indicate that the microbial reduction of magnetite NPs deserves attention when natural magnetites are used in paleoenvironment reconstruction. Key Points: Microbially reduced magnetite nanoparticles (NPs) have larger lattice parameters compared to pristine ones Microbial reduction of magnetite NPs leads to a softer magnetism and increasing magnetic susceptibility Partially oxidized magnetite is resistant to bioreduction